INTEGRATING GHRM AND INFORMATION SYSTEMS FOR SUSTAINABILITY IN OIL & GAS: 2019-2023 BIBLIOMETRIC STUDY - Rachman, Adryan; Diandra, Nadia; Anthony, Gerald Ethan (Jurnal Teknik Informatika (Jutif), 2024)
In an era where ecological sustainability intersects with corporate accountability, this study pioneers the integration of Green Human Resource Management (GHRM) practices within the oil and gas sector, heralding a paradigm shift towards environmental stewardship and sustainable business operations. Through an incisive bibliometric analysis of data sourced from Scopus, ScienceDirect, and ResearchGate databases covering the years 2019-2023, this research meticulously examines a corpus of 52 journals, selectively narrowing down to 10 seminal works that underscore the critical nexus between organizational strategies and sustainable investment practices. Leveraging the analytical prowess of VosViewer for a nuanced exploration of the thematic landscape, this study illuminates the transformative role of GHRM in driving the oil and gas industry towards a future where environmental considerations are not merely an adjunct to business strategy but are embedded within the core operational ethos. The investigation transcends conventional academic discourse, positioning itself as a clarion call for the industry to reevaluate and realign its project management and investment frameworks in favor of sustainable development principles. The findings of this research are both a testament to and a roadmap for the integration of sustainability into the fabric of corporate strategy, highlighting innovation, strategic adaptability, and a steadfast commitment to green practices as indispensable to securing the sector’s long-term viability. This study not only contributes to the burgeoning field of GHRM but also sets a benchmark for future research, advocating for a symbiotic relationship between economic growth and environmental preservation. This groundbreaking work challenges the oil and gas sector to lead by example, embodying the principles of sustainability in every facet of its operations, thereby setting a new standard for corporate responsibility in the face of global ecological challenges.